2003
DOI: 10.1002/chir.10266
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective single‐dose kinetics of citalopram and its metabolites in rats

Abstract: The single-dose kinetics of the enantiomers of citalopram (CIT) and its metabolites, demethylcitalopram (DCIT) and didemethylcitalopram (DDCIT), were investigated after administration of 10, 20, or 100 mg/kg (s.c.) rac-CIT to rats. Samples from serum and two brain regions were collected 1, 3, 10, or 20 h postdose for HPLC analysis. In the 100 mg/kg rats, the enantiomeric (S/R) serum concentration ratios of CIT decreased during the study period (0.93 at 1 h vs. 0.59 at 20 h; P < 0.001). In the 10 and 20 mg/kg r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…The total loss of P-gp might change the volume of distribution which can influence the drug elimination (Endres et al, 2006). These enantiomeric ratios are much higher compared to corresponding ratios in humans and rats (S/R ratios of 0.59 in patients and around 0.9 in rats given 10 mg/kg citalopram) indicating possible species differences Kugelberg et al, 2001Kugelberg et al, , 2003. When comparing S/R ratios, there can be a stereoselective metabolism in mice not seen in humans or the opposite situation.…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 99%
“…The total loss of P-gp might change the volume of distribution which can influence the drug elimination (Endres et al, 2006). These enantiomeric ratios are much higher compared to corresponding ratios in humans and rats (S/R ratios of 0.59 in patients and around 0.9 in rats given 10 mg/kg citalopram) indicating possible species differences Kugelberg et al, 2001Kugelberg et al, , 2003. When comparing S/R ratios, there can be a stereoselective metabolism in mice not seen in humans or the opposite situation.…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 99%
“…This is similar to data observed after a neonatal treatment with other SSRIs (Hansen et al, 1997;Maciag et al, 2006a,b). Interestingly, the rapidly metabolized citalopram was less efficient than slowly metabolized fluoxetine (Geczy et al, 2000;Kugelberg et al, 2003;Ansorge et al, 2008) to induce deficits in novelty-induced tests of behavioral inhibition (which are sensitive to mild increases in anxiety) (Ansorge et al 2008). This suggests that a stronger or sustained increase in brain serotonin compared with that induced by escitalopram may be required to produce anxiety (see also Gross et al, 2002).…”
Section: Depression-and Anxiety-like Behaviorsmentioning
confidence: 99%
“…7 Kugelberg et al 8 reported S/R plasma concentration ratios of 0.94, 0.83, and 0.34 for CITA and of 0.85, 0.37, and 0.36 for DCITA in rats treated with multiple doses of 10, 20, and 100 mg CITA/kg/day for 10 days, respectively, suggesting that a dose increase reduces the S/R ratio of CITA and DCITA. Kugelberg et al 9 demonstrated enantioselectivity in the metabolism of CITA in rats receiving subcutaneous administration of a single dose of 20 or 100 mg/kg. The authors reported S/R plasma concentration ratios of 0.7 and 0.6 for CITA 10 and 20 h after administration of the racemic drug, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…In the two studies, CITA was administered with an osmotic pump, i.e., the absorption process was devoid of presystemic elimination. Kugelberg et al 9 observed enantioselectivity in the metabolism of CITA in rats subcutaneously injected with a single dose of 20 or 100 mg/kg. The authors reported S/R plasma concentration ratios of 0.6 for CITA, 20 h after administration of the drug.…”
mentioning
confidence: 98%